Living with interpersonal data: observability and accountability in the age of pervasive ICT - Goulden, Murray; Tolmie, Peter; Mortier, Richard; Lodge, Tom (SAGE, 2017)
The Internet of Things, alongside existing mobile digital technologies, heralds a world in which pervasive sensing constantly captures data about us. Simultaneous with this technology programme are moves by policymakers to shore up the digital economy through the legislating of new trust-building models of data management. These moves seek to give individuals control and oversight of their personal data. Within shared settings, the consequences of these changes are the large-scale generation of interpersonal data generated by and acting on the group rather than individual. We consider how such systems create new forms of observability and hence accountability among members of the home, and draw on the work of Simmel and Goffman to explore how these demands are managed. Such management mitigates the more extreme possibilities for domestic monitoring posited by these systems, yet without careful design there remains a considerable danger of unanticipated negative consequences.